Effects of subject‐oriented visualization tools on search by novices and intermediates. - Wu, I‐Chin; Vakkari, Pertti (Journal of the Association for Information Science & Technology, 2018)
This study explores how user subject knowledge influences search task processes and outcomes, as well as how search behavior is influenced by subject‐oriented information visualization (IV) tools. To enable integrated searches, the proposed WikiMap+ integrates search functions and IV tools (i.e., a topic network and hierarchical topic tree) and gathers information from Wikipedia pages and Google Search results. To evaluate the effectiveness of the proposed interfaces, we design subject‐oriented tasks and adopt extended evaluation measures. We recruited 48 novices and 48 knowledgeable users, that is, intermediates, for the evaluation. Our results show that novices using the proposed interface demonstrate better search performance than intermediates using Wikipedia. We therefore conclude that our tools help close the gap between novices and intermediates in information searches. The results also show that intermediates can take advantage of the search tool by leveraging the IV tools to browse subtopics, and formulate better queries with less effort. We conclude that embedding the IV and the search tools in the interface can result in different search behavior but improved task performance. We provide implications to design search systems to include IV features adapted to user levels of subject knowledge to help them achieve better task performance.